Differential expression of PSD proteins in age-related spatial learning impairments - Nyffeler, Myriel; Zhang, Wei-Ning; Feldon, Joram; Knuesel, Irene (Neurobiology of aging, 2007)
Deficits in hippocampus-dependent spatial learning that are typical for a subpopulation of aged rats are not associated with loss of neurons or excitatory synapses but accompanied by significant reduction of postsynaptic density (PSD) area in perforated synapses. Here, we examined whether structural alterations in aged learning-impaired rats correlate with altered content of PSD proteins which are critically involved in normal synaptic function. Spatial memory tasks were used to separate male rats into young, aged learning-unimpaired and impaired groups. Semi-quantitative immunohistochemistry revealed significant alterations in the content of the AMPA receptor GluR1 subunit, PSD-95 and synGAP in the hippocampal formation of aged-learning impaired compared to aged-unimpaired and young rats. While synGAP expression was reduced, GluR1 and PSD95 levels were selectively increased in aged-learning-impaired subjects. These findings suggest that age-induced changes of the PSD protein expression levels are more pronounced in learning-impaired rats compared to unimpaired subjects and that the alterations in synaptic protein content may result in reduced synaptic function, potentially underlying the individual differences in mnemonic functions during aging.